Modelos para análise e dimensionamento de painéis de alvenaria estrutural - Damasceno, Júlio César Cavalcante (2012)
The main objective of this thesis was the study of bracing panels of structural masonry, by applying the Finite Element Method and Strut and Tie Method. It was analyzed the following aspects: the effect of orthotropy on the behavior of the panels; distribution of horizontal forces between panels for buildings; comparison between Equivalent Frame and Finite Elements models; panels design with the Strut and Tie Method. The results showed that one should not disregard the orthotropy, otherwise this can lead to models stiffer than the real. Regarding the distribution of horizontal forces, showed that the disregard of lintels and shear deformation leads to significant differences in the simplified model. The results showed also that the models in Finite Element and Equivalent Frame exhibit similar behavior in respect to stiffness of panels and stress distribution over the sessions requested. It was discussing criteria for designing Strut and Tie Method models in one floor panels. Then, the theoretical strength these panels was compared with the rupture strength of panels tested in the literature. The theoretical maximum strength were always less than the rupture strength of the panels obtained in tests, due to the fact that the proposed model cannot represent the behavior of the masonry after the start of the panel cracking due to plasticization of the reinforcement